A Review of College Student in Physics Education: Type, Cause and Remediation Misconception - Adimayuda, Rizal; Suhandi, Andi; Samsudin, Achmad; Suhendi, Endi; Setiawan, Agus; Fratiwi, Nuzulira Janeusse; Kapici, Hasan Ozgur (Yayasan Keluarga Guru Mandiri, 2026)
Misconceptions in physics education continue to pose significant challenges to meaningful learning among college students. This study aims to analyze the types, causes, and remediation strategies of physics misconceptions at the tertiary level through a systematic literature review. A total of 50 peer-reviewed articles published between 2019 and 2023 were selected from the Scopus database using bibliometric analysis tools, including Harzing's Publish or Perish and VosViewer. The review reveals five main types of student misconceptions: prejudice-based, non-scientific theories, conceptual misconceptions, vernacular misunderstandings, and factual errors. The most common causes include students' prior knowledge and ineffective instructional methods. The four-tier diagnostic test is found to be the most frequently used and effective tool in identifying misconceptions. Remediation strategies include conceptual change texts, simulation-based experiments, e-learning, and collaborative learning models. The study concludes that understanding and addressing misconceptions require both accurate diagnostic tools and innovative teaching strategies. This review contributes to physics education research by providing a comprehensive overview of misconception diagnostics and remediation approaches over the past five years.